2008
DOI: 10.1111/j.1752-1688.2008.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Variability and Trends in Pesticide Concentrations in Streams1

Abstract: A parametric regression model was developed for assessing the variability and long‐term trends in pesticide concentrations in streams. The dependent variable is the logarithm of pesticide concentration and the explanatory variables are a seasonal wave, which represents the seasonal variability of concentration in response to seasonal application rates; a streamflow anomaly, which is the deviation of concurrent daily streamflow from average conditions for the previous 30 days; and a trend, which represents long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…Flow anomalies (FA) are dimensionless, orthogonal time series calculated from measured daily discharge that describe the variability in stream discharge at different time scales (e.g. 1 day, 30 days, 1 year; Vecchia et al, 2008). Flow anomalies have been found to be correlated to the observed variability of concentrations of pesticides and nutrients in other studies (Vecchia et al, 2008;Ryberg et al, 2010), and therefore were expected to add significant explanatory power to the regressions used to predict SC.…”
Section: Regression-derived Daily Scmentioning
confidence: 98%
“…Flow anomalies (FA) are dimensionless, orthogonal time series calculated from measured daily discharge that describe the variability in stream discharge at different time scales (e.g. 1 day, 30 days, 1 year; Vecchia et al, 2008). Flow anomalies have been found to be correlated to the observed variability of concentrations of pesticides and nutrients in other studies (Vecchia et al, 2008;Ryberg et al, 2010), and therefore were expected to add significant explanatory power to the regressions used to predict SC.…”
Section: Regression-derived Daily Scmentioning
confidence: 98%
“…In this study, a statistical model is used to quantify the unexplained variability in nitrate concentration after filtering out these effects. This unexplained variability is the deviation of the observed log nitrate concentration from the log nitrate concen- tration predicted by a statistical model (based on contemporaneous daily mean flow, season, and trend), herein referred to as nitrate anomalies (Vecchia et al, 2008). To evaluate if antecedent flow conditions can help to explain variations in nitrate concentrations, we tested whether nitrate anomalies were significantly (alpha = 0.05) related to a measure of antecedent flow conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies show that antecedent moisture conditions influence nutrient export from river basins (Burt and Worrall, 2009;Garrett, 2012;Macrae et al, 2010;Soulsby et al, 2003;Vecchia et al, 2008;Lucey and Goolsby, 1993). Commonly, studies document increased nutrient export following a prolonged dry period (Foster and Walling, 1978;Macrae et al, 2010), though some studies have observed the opposite effect when considering only more recent antecedent conditions (Creed and Band, 1998;Macrae et al, 2010;Welsch et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…; N, let LF t ¼ log F t ð Þ. 2) Short-term flow anomaly [8]. For flow F t , the short-term flow anomaly SF t is defined as …”
Section: Model Developmentmentioning
confidence: 99%